Collecting and Integrating National Laws and Regulations on Construction in Coastal Areas - Malekshahi, Mahtab (2021)
Instructions for designing coastal structures in order to create coordination and uniformity in the criteria for designing, constructing, supervising and executing coastal structures and projects subject to that instruction, as well as observing the principles, methods and technologies appropriate to the applied equipment and compatible with the conditions and requirements. So present study aimed to collecting and integrating national laws and regulations on construction in coastal areas was performed. Descriptive and analytical method is a suitable method for the present study. The study method in the research is library method and is a tool for collecting information from valid domestic and foreign sources.Also, the publication has been tried to be compiled in such a way that due to the limited access to the texts of standards and regulations and in order to expand the culture of technical knowledge and transfer it to the design and implementation factors of projects, the content of applicable instructions and technical criteria to be available to users as much as possible. Compilation of comprehensive instructions for designing coastal structures with all its positive features seems necessary to design specific instructions for Iran in accordance with environmental conditions. However, in the current situation where other guidelines are used as a basis, it is necessary for the academic education system to move in this direction and identify the shortcomings and deficiencies of this foreign guideline and rewrite it based on local characteristics.